2023
DOI: 10.1111/pbi.14076
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of qAHPS07 and functional studies of AhRUVBL2 controlling pod size in peanut (Arachis hypogaea L.)

Abstract: SummaryCultivated peanut (Arachis hypogaea L.) is an important oil and cash crop. Pod size is one of the major traits determining yield and commodity characteristic of peanut. Fine mapping of quantitative trait locus (QTL) and identification of candidate genes associated with pod size are essential for genetic improvement and molecular breeding of peanut varieties. In this study, a major QTL related to pod size, qAHPS07, was fine mapped to a 36.46 kb interval on chromosome A07 using F2, recombinant inbred line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…QTLs for traits that are positively or negatively correlated tended to co-localize in the same or adjacent genomic regions Earlier research indicated PST is strongly positively correlated with PA, PL, and PW [10]. In the current study, the correlation analysis of 350 individuals revealed the highly positive correlations among PST, PA, PL, and PW, but these traits were only weakly positively correlated with PP.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…QTLs for traits that are positively or negatively correlated tended to co-localize in the same or adjacent genomic regions Earlier research indicated PST is strongly positively correlated with PA, PL, and PW [10]. In the current study, the correlation analysis of 350 individuals revealed the highly positive correlations among PST, PA, PL, and PW, but these traits were only weakly positively correlated with PP.…”
Section: Discussionsupporting
confidence: 40%
“…Liu QTLs on chromosomes 4, 7, and 13 (PVE of 7.36-11.61%) [9]. In a recent study, one stable major QTL for PST (qAHPS07) was nely mapped to a 36.46-kb physical interval on chromosome 7 [10]. However, PST measurements are generally imprecise and the complex genetic mechanisms underlying this trait remain relatively uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al examined the 267 lines of a RIL population derived from Yueyou92 and Xinhuixiaoli and detected three QTLs on chromosomes 4, 7, and 13 (PVE of 7.36–11.61%) [ 9 ]. In a recent study, one stable major QTL for PST ( qAHPS07 ) was finely mapped to a 36.46-kb physical interval on chromosome 7 [ 10 ]. However, PST measurements are generally imprecise and the complex genetic mechanisms underlying this trait remain relatively uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, advances in next-generation sequencing technologies and decreases in sequencing costs have enabled researchers to gradually develop and improve BSA sequencing (BSA-seq) methods and technical systems for analyses of multiple crops, including maize [ 12 ], soybean [ 13 ], rice [ 14 ], and wheat [ 15 ]. They have also been used in studies on various peanut traits, including testa color [ 16 ], branch number [ 17 ], sucrose content [ 18 ], and pod size [ 10 ].…”
Section: Introductionmentioning
confidence: 99%